The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.14419/ijdr.v5i2.8224
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of partial edentulism among young Saudi women of Qassim and their perception of early tooth loss

Abstract: Background: Edentulism and number of remaining teeth per capita are commonly used as main indicators of dental health status in national surveys. Objectives: To determine the level of tooth loss and the most common arch affected, to find the out awareness level of replacement of missing teeth with different prosthetic types and to evaluate the correlation between educational level and tooth loss. Subjects and methods: This was cross-sectional clinical examination, and questionnaire based study, examining the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
3
7
0
Order By: Relevance
“…Most of the subjects in this study obtained a primary level of education (282, 44.1%), followed by the illiterate (182, 28.4%) as shown in Table IV. This finding was consistent with that of other studies 3,13 determining and providing the needs of the population regarding different types of prostheses for missing teeth.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Most of the subjects in this study obtained a primary level of education (282, 44.1%), followed by the illiterate (182, 28.4%) as shown in Table IV. This finding was consistent with that of other studies 3,13 determining and providing the needs of the population regarding different types of prostheses for missing teeth.…”
Section: Discussionsupporting
confidence: 93%
“…Dental caries, periodontitis (disease surrounding the soft tissue of the tooth), trauma, and/or a combination of these disorders are the common causes of tooth loss. [1][2][3] On the basis of potential combinations of teeth to ridges, various methods of partial edentulism classification have been reported in different dental studies and surveys. At present, Kennedy classification is the most accurate and widely used and accepted because of its simplicity, ease of application to all partial edentulous situations, immediate visualization of the type of partially edentulous arch being considered, and differentiation between tooth-borne and tooth-tissue-borne removable partial dentures.…”
Section: Introductionmentioning
confidence: 99%
“…4 In the study, class III was the most common in both maxilla (59%) and mandible (61%) which is similar to the study conducted in Pakistan with 54% in maxilla and 53% in mandible whereas class IV was the least common in both maxilla (1%) and mandible (6%) which is in parallel with the same study with maxilla (9%) and mandible (5%). 5 The majority of Kennedy's class I was without modification in both maxilla (10) and mandible (10) which is in agreement with other studies 6,7 where as it contradicts with the study conducted in Nepal Medical College and Teaching Hospital. 10 Likewise the majority of Kennedy's class III are also without modification in both maxilla (56) and mandible (52) which is in agreement with other studies.…”
Section: Discussionsupporting
confidence: 59%
“…10 Likewise the majority of Kennedy's class III are also without modification in both maxilla (56) and mandible (52) which is in agreement with other studies. 6,7 In this study 34.9% patients had left mandibular first molar missing, 25.3% people had right mandibular second molar missing and 24.3% people had right maxillary second molar as well as permanent right mandibular first molar missing respectively. This frequency of molar missing is contradicting with the study conducted in India.…”
Section: Discussionmentioning
confidence: 50%
“…The loss of many teeth usually affects the quality of life and has a negative impact on the functional, social and psychological well-being of an individual. 1 Generally, it occurs by caries, periodontal problems, traumatic injuries, impactions, and supernumerary teeth, neoplastic and cystic lesions. Some studies have reported caries as the main causative agent for tooth loss.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%